Perceived Personal Control Buffers Terminal Decline in Well-Being - Denis Gerstorf; Jutta Heckhausen; Nilam Ram; Frank J. Infurna; Jürgen Schupp; Gert Wagner (Psychology and Aging, 2014)
Recent research has repeatedly demonstrated that well-being typically evinces precipitous deterioration close to the end of life. However, the determinants of individual differences in these terminal declines are not well understood. In this study, we examine the role of perceived personal control as a potential buffer against steep terminal declines in well-being. We applied single- and multiphase growth models to up to 25-year longitudinal data from 1,641 now-deceased participants of the national German Socio-Economic Panel Study (SOEP; age at death: M = 74 years; SD = 14; 49% women). Results revealed that perceiving more personal control over one's life was related to subsequently higher late-life well-being, less severe rates of late-life declines, and a later onset of terminal decline. Associations were independent of key predictors of mortality, including age, gender, SES, and disability. These findings suggest that feeling in control may ameliorate steep end-of-life decline in well-being. We also discuss scenarios for when and how processes of goal disengagement and giving up control may become beneficial.
Additional information: This article may not exactly replicate the final version published in the APA journal “Psychology and Aging” at http://dx.doi.org/10.1037/a0037227. It is not the copy of record.
Keywords: 330; Successful aging; differential aging; control perceptions; control strivings; multiphase growth model; mortality; German Socio-Economic Panel Study; SOEP; Zufriedenheit; Alte Menschen; Panelforschung